Synthesis and characterization of poly (methyl methacrylate)/ silver-doped hydroxyapatite dip coating on Ti6Al4V - Bansal G.; Gautam R.K.; Misra J.P.; Mishra A. (My University, 2025)
This study intends to analyze the properties and potential applications of a novel composite coating composed of poly (methyl methacrylate) (PMMA) and silver-doped hydroxyapatite (HAPAg) produced from waste eggshells, which was dip-coated onto Ti6Al4V substrates. Medical implants frequently made of the titanium alloy Ti6Al4V can benefit greatly from surface coatings in terms of biocompatibility and performance. In order to add antibacterial and osteoconductive characteristics, silver-doped hydroxyapatite nanoparticles were dispersed within a PMMA matrix to create the PMMA/HAPAg composite coating. The coated samples report an average contact angle (CA) between 70 and 750 and total surface free energy (SFE) between 35 and 50 mJ/m2, which signifies its improved wettability. The 7.03% change in hydrophilicity was observed between PMMA/H0 (75.270 ± 1.690) and PMMA/H20 (700 ± 1.440) coated samples. The increase in adhesion strength and coating thickness with the increase in HAPAg reinforcement was observed. The surface morphology of the defective zones was examined using scanning electron microscopy (SEM), and information on the elemental composition of synthesized was obtained using Inductively Coupled Plasma Mass Spectroscopy (ICPMS), Fourier Transform Infrared spectroscopy (FTIR) and X-ray diffractogram (XRD). Atomic force microscopy (AFM) reveals the surface roughness; root mean square roughness, roughness profile, skewness and kurtosis of the coated samples. The contact angle reports the hydrophilicity and SFE. Finally, the results conclude that the composite coating had a consistent distribution of HAPAg nanoparticles incorporated within the PMMA matrix. The minimal presence of Ag ions on the surface indicates the coating's potential antibacterial properties, and it is highly recommended for dental applications. © 2024 Elsevier B.V.